2014
DOI: 10.1111/1365-2664.12320
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity networks reveal the risks of crown‐of‐thorns starfish outbreaks on the Great Barrier Reef

Abstract: Summary1. Many ecosystems suffer systemwide outbreaks of damaging species propagating from primary outbreak sites. Connectivity patterns can identify parts of the ecosystem that help turn local outbreaks into a systemwide contagion through a series of transmission events. Here, we show that patterns of larval connectivity among reefs can help explain periodic crown-ofthorns starfish (COTS) epidemics across the Great Barrier Reef (GBR). 2. We simulated potential dispersal of COTS larvae to obtain a connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
125
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 48 publications
2
125
1
Order By: Relevance
“…However, the spread of population outbreaks, determined based on field surveys Miller 2000;Vanhatalo et al 2016) and modelling (Dight et al 1990a(Dight et al , 1990bReichelt et al 1990;Black and Moran 1991; Black 1993;Hock et al 2014;Vanhatalo et al 2016) shows that at least some larvae must be dispersed and settle on non-natal reefs, regardless of the presence of adult CoTS. Improvements in hydrodynamic models, combined with advances in computational power and new methods for analysing patterns of particle dispersal, are providing increasingly resolved and tractable models to inform patterns of initiation and spread for CoTS outbreaks (Dight et al 1990a(Dight et al , 1990bBlack et al 1995;Hock et al 2014;Hock and Mumby 2015). However, these models are potentially very sensitive to the precise timing of spawning and the relevant speed and direction of currents, and predictions arising from these models need explicit testing based on extensive spatial and temporal sampling to resolve the occurrence and timing of outbreaks.…”
Section: Question 8 and 14 (Larvae And Juveniles) -What Factors Are Impmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the spread of population outbreaks, determined based on field surveys Miller 2000;Vanhatalo et al 2016) and modelling (Dight et al 1990a(Dight et al , 1990bReichelt et al 1990;Black and Moran 1991; Black 1993;Hock et al 2014;Vanhatalo et al 2016) shows that at least some larvae must be dispersed and settle on non-natal reefs, regardless of the presence of adult CoTS. Improvements in hydrodynamic models, combined with advances in computational power and new methods for analysing patterns of particle dispersal, are providing increasingly resolved and tractable models to inform patterns of initiation and spread for CoTS outbreaks (Dight et al 1990a(Dight et al , 1990bBlack et al 1995;Hock et al 2014;Hock and Mumby 2015). However, these models are potentially very sensitive to the precise timing of spawning and the relevant speed and direction of currents, and predictions arising from these models need explicit testing based on extensive spatial and temporal sampling to resolve the occurrence and timing of outbreaks.…”
Section: Question 8 and 14 (Larvae And Juveniles) -What Factors Are Impmentioning
confidence: 99%
“…Elevated nutrients may therefore, be a necessary precursor for outbreaks to become established, but there are other conditions that must also be met. Modelling studies by Wooldridge and Brodie (2015) suggested that it is inter-annual variation in levels of larval retention (see Hock et al 2014) that may explain when, and perhaps where, primary outbreaks become established. Importantly, hydrodynamic conditions would have promoted high levels of self-recruitment (rather than dispersal of larvae among widely separated reefs) in years prior to outbreaks arising in 1979(Wooldridge and Brodie 2015.…”
mentioning
confidence: 99%
See 3 more Smart Citations